2009
DOI: 10.4314/aga.v19i2.1714
|View full text |Cite
|
Sign up to set email alerts
|

Production D\'alevins De Tilapia (<i>Oreochromis niloticus</i> L., 1758) nourris avec des sous-produits agricoles, sans adjonction de farine de poisson

Abstract: Deux lots d'alevins du tilapia Oreochromis niloticus (14 ± 6 mg et 1660 ± 8 mg, respectivement) ont été nourris avec3 aliments (A1, A2 et A3) formulés uniquement à base de sous-produits agricoles et un aliment industriel commercial contenant de la farine de poisson servant de témoin (At). Les alevins de 14 ± 6 mg et 1660 ± 8 mg ont été mis dans des bassins, à des densités respectives de 1667 et 500 ind/m 2. Deux essais expérimentaux ont été réalisés. Les résultats de l'élevage post-larvaire (14 ± 6 mg) montren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
5
2
3
Order By: Relevance
“…The linear specific growth rates recorded in the present study are similar to those reported for Oreochromis niloticus by [24] in Ivorian lagoons (0.48 % day -1 ). The nutritive quotients recorded in this study are higher than those observed by [48], [55] in fish tanks and ponds to "Côte d'Ivoire". Indeed, depending on the alimentary treatment, fry of Oreochromis niloticus subjected to a diet without fish meal have shown the nutritive quotients of 0.98 and 1.3 in the rearing tanks [55].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The linear specific growth rates recorded in the present study are similar to those reported for Oreochromis niloticus by [24] in Ivorian lagoons (0.48 % day -1 ). The nutritive quotients recorded in this study are higher than those observed by [48], [55] in fish tanks and ponds to "Côte d'Ivoire". Indeed, depending on the alimentary treatment, fry of Oreochromis niloticus subjected to a diet without fish meal have shown the nutritive quotients of 0.98 and 1.3 in the rearing tanks [55].…”
Section: Discussioncontrasting
confidence: 75%
“…The nutritive quotients recorded in this study are higher than those observed by [48], [55] in fish tanks and ponds to "Côte d'Ivoire". Indeed, depending on the alimentary treatment, fry of Oreochromis niloticus subjected to a diet without fish meal have shown the nutritive quotients of 0.98 and 1.3 in the rearing tanks [55]. Oreochromis niloticus fingerlings reared under the stocking densities of 10 individuals m -2 and 13 individuals m -2 showed the nutritive quotients ranging from 1.13 to 1.87 [48].…”
Section: Discussioncontrasting
confidence: 75%
“…In Côte d'Ivoire, the development of high-quality low-cost feeds for fish farmers has become a priority for many scientists. Previous works made by Bamba et al [21,22] and Koumi et al [23,24] on O. niloticus feeds, although based on local raw materials, were not specific to the areas of the high concentration of fish farmers. However, the different areas of fish farming practices in Côte d'Ivoire were well identified by [5] and availability and costs of raw materials vary by region and by area in the same country.…”
Section: Introductionmentioning
confidence: 98%
“…However, [14] and [15] indicate that the major constraints to the emergence of fish farming are high-cost nutrition and the lack of national fish farming policies. In fact, fish farmers are confronted with certain problems, in particular, the low yields of fish farming activities linked to the difficulties of feeding fish and the lack of fry, the weakness of technical supervision and the low funding of the sector [16].…”
Section: Introductionmentioning
confidence: 99%